KOMUNIKASI INTERPERSONAL KAUM LESBIAN DI KAWASAN MC DONALD’S MANADO - Weydekamp, Christa Melisa (ACTA DIURNA KOMUNIKASI, 2013)
The interpersonal communication has an important role towards the development of lesbian behavior in relation with other persons. There are some of lesbian persons state their private information state their private information as lesbians in the collective boundary, and some other lesbian persons in the personal boundary, so that the information’s lesbian persons still hidden and not opened to the many peoples. Keywords : Interpersonal Communication, Lesbian Persons and Behavior